2023
DOI: 10.1371/journal.pone.0281517
|View full text |Cite
|
Sign up to set email alerts
|

Pain phenotyping and investigation of outcomes in physical therapy: An exploratory study in patients with low back pain

Abstract: Phenotypes have been proposed as a method of characterizing subgroups based on biopsychosocial factors to identify responders to analgesic treatments. This study aimed to, first, confirm phenotypes in patients with low back pain receiving physical therapy based on an a priori set of factors used to derive subgroups in other pain populations. Second, an exploratory analysis examined if phenotypes differentiated pain and disability outcomes at four weeks of physical therapy. Fifty-five participants completed psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Numerous studies have conducted phenotyping analyses in patients with LBP using a variety of methods and patient-level variables. 27,[53][54][55] For chronic LBP specifically, a recent systematic review found 43 studies, 56 with the number of phenotypes identified ranging from two to nine per study. 54,56 The large majority of studies identified three to four phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have conducted phenotyping analyses in patients with LBP using a variety of methods and patient-level variables. 27,[53][54][55] For chronic LBP specifically, a recent systematic review found 43 studies, 56 with the number of phenotypes identified ranging from two to nine per study. 54,56 The large majority of studies identified three to four phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample included patients with varying acuity of LBP, likely increasing its applicability for primary care settings that see a spectrum of patients with acute to chronic presentations. Prior studies have explored LBP phenotypes in cohorts representing worker's compensation, 53 university‐based health systems, 27 and county 1,54 and national osteoarthritis registries 55 . None have assessed phenotypes in beneficiaries of the MHS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The evaluation of multiple domains of psychological distress including depression, anxiety, and pain catastrophizing allows for increased effectiveness and efficiency in discriminating between patients who may be at risk for poor outcomes. This comprehensive evaluation also allows for classifying pain phenotypes and identifying those who would benefit from targeted treatment interventions such as cognitive behavioral therapy or psychologically informed treatment [77][78][79]. Due to this, considering a multidimensional tool which evaluates a global psychological profile would inform a clinician if specific targeted interventions would be beneficial for their patient.…”
Section: Discussionmentioning
confidence: 99%